Evaluating respiratory musculature, quality of life, anxiety, and depression among patients with indeterminate chronic Chagas disease and symptoms of pulmonary hypertension - Suman, Alicia Cristina [UNESP]; Pellison Nunes da Costa, Erika Alessandra [UNESP]; Zanati Bazan, Silmeia Garcia [UNESP]; Hueb, Joao Carlos [UNESP]; Carvalho, Fabio Cardoso de [UNESP]; Martin, Luis Cuadrado [UNESP]; Yoo, Hugo Hyung Bok [UNESP] (Soc Brasileira Medicina Tropical, 2017)
Introduction: Chagas disease (CD) is progressive and incapacitating, especially when cardiopulmonary function is affected. For example, respiratory muscle weakness can cause dyspnea upon exertion and fatigue, which may be exacerbated when it is associated with pulmonary hypertension (PH). The present study aimed to evaluate respiratory musculature, quality of life, anxiety, and depression among patients with indeterminate chronic CD and symptoms of PH. Methods: All individuals completed a clinical evaluation, spirometry, a 6-min walking test, respiratory musculature testing using maximum inspiratory pressure (PImax) and maximum expiratory pressure (PEmax), the Hospital Anxiety and Depression Scale, and the SF-36 questionnaire. Results: We evaluated 107 patients who were assigned to a control group with only CD (G1, 8 patients), a group with CD and possible PH (G2, 93 patients), and a group with CD and echocardiography evidence of PH (G3, 6 patients). The three groups had similar values for PImax and PEmax. Compared to the G1 and G2 groups, the G3 group covered significantly less distance during the 6-min walking test and had a significantly shorter predicted distance (p < 0.05 vs. the G1 group). All three groups had similar values for their spirometry results, Hospital Anxiety and Depression Scale scores, and SF-36 questionnaire results. Conclusions: Patients with indeterminate chronic CD and symptoms of PH did not experience significant impairment in the studied variables, with the exception of the 6-min walking test, which suggests a low exercise tolerance.
Keywords: Chagas disease; Pulmonary hypertension; Quality of life; Respiratory musculature